FERTILITAS DAN RELASI GENDER DI DESA NEGLASARI, KABUPATEN BOGOR - Ekowati, Dian; Sri, Ekawati; Rusli, Said (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2012)
Fertility is often seen on the figures and biological sides. Seeing fertility goes beyond both of these will be useful to explore the wishes of each actor , how they relate to each other and to the community , and how the values and aspects of sociological and psychological that is attached in such activities. The study explored how the relationship between gender relations and fertility work ; especially because until now there is no generic theory agreed to this issue . This study used qualitative methods to explore and gain an understanding of how women give birth as related parties with the other actors . The framework of this study were made by utilizing research - research that has been done before , namely the concept of female autonomy ( Mason and Smith , 2003) and the concept of the determinant ( Bongaarts , 1978) . The concept is referred to aspects of women's autonomy is the power of women to make household economic decisions , the power of women to make decisions about family size , women freedom of movement , individual attitudes toward gender attitude of the community , and the movement of women in decision-making ( Mason and Smith , 2003 . Determinants required for connecting between socio - economic variables - culture with fertility because after all , there are facts that can not be denied that fertility is the result of biological activity . The results showed that although the values at the community level suggested to have the number of children that a lot , to a certain extent , the women in the study area can control the number of children they have. This control works through Desired fertility and the determinants , namely : the use of contraception and delay the age of marriage is influenced by women's autonomy and power as proposed by Mason and Smith ( 2003) . Women's autonomy and power in question is the power of women in economic decision-making , decision-making power of women in family size , their physical freedom of movement , the size of the gender attitudes at the community level , and their space in household decisionmaking . The conclusion of this study indicate that in the study area , the use of contraception is more influential in affecting fertility than the actual delay marriage age. Keywords : Gender Relationships, Fertility, Aspects of Women's Autonomy and Power , Desired Fertility, Actual Fertility, Reuters Determinants